Customer's Decisions To Save In Sharia Banking Among Jakarta Millennial - Adelia Irmawanti; Rosana Eri Puspita (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
This study aims to analyze what factors influence a customer's decision to save at a sharia bank, especially in the DKI Jakarta. The variables of knowledge, religiosity, and promotion. The intention-to-save is the mediating variables. This study uses a quantitative approach with primary data collected through a questionnaire with a purposive sampling technique. The number of samples used in the study was 400 respondents who were customers of all Islamic banks in Jakarta. Data analysis used the SPSS 20 application. The results showed that knowledge, religiosity and promotion had a positive and significant effect on the intention-to-save. The intention has a positive and significant effect on customer decisions. Knowledge, religiosity and promotion have a positive and significant effect on saving decisions. And the last, intention-to-save, can mediate knowledge, religiosity and promotion of saving decisions. Islamic banks must continue to improve each of the customer's determinants to improve Islamic banks' existence.